Development of a Five-Day Basic Microsurgery Simulation Training Course: A Cost Analysis - Singh, Masha (The Korean Society of Plastic and Reconstructive Surgeons, 2014)
The widespread use of microsurgery in numerous surgical fields has increased the need for basic microsurgical training outside of the operating room. The traditional start of microsurgical training has been in undertaking a 5-day basic microsurgery course. In an era characterised by financial constraints in academic and healthcare institutions as well as increasing emphasis on patient safety, there has been a shift in microsurgery training to simulation environments. This paper reviews the stepwise framework of microsurgical skill acquisition providing a cost analysis of basic microsurgery courses in order to aid planning and dissemination of microsurgical training worldwide.